A prospective study of risk stratification in patients undergoing emergency laparotomy with POSSUM and P-POSSUM - Jain, Ajay Kumar; Sharma, Dhiraj (International Surgery Journal, 2016)
Background: Physiological and operative severity score for enumeration of mortality and morbidity (POSSUM) and its Portsmouth modification (P-POSSUM) have been developed and validated in many studies to assess the risk of mortality and morbidity associated with the various surgical procedures. Prediction of risk of mortality and morbidity involved in a surgical procedure not only helps clinicians in adequate preparation but also patient counselling. Methods: One hundred and seven consecutive patients who underwent emergency laparotomy in the year 2009 at our center were studied. Mortality and Morbidity risk were calculated in each using POSSUM and P-POSSUM. The ratio of observed to predicted death and morbidity (0: E) were calculated and compared using chi square test. Serum creatinine level and delay in presentation to hospital were also noted in each as adjuncts variables. Results: POSSUM was found to over predict both mortality and morbidity (O: E = 0.44 and 0.66 respectively). P-POSSUM accurately predicted mortality (O: E =0.98). Both POSSUM and P-POSSUM over predicted mortality in low risk groups (predicted risk of mortality <20%, O: E= 0.00 and 0.34 respectively). Average serum creatinine levels and delay in presentation to hospital among patients who survived and those who expired were 1.67 & 2.42 mg/dl and 2.04 & 2.89 days respectively. Conclusions: Although both equations are useful tools for risk-adjusted surgical audit of patients undergoing emergency laparotomy, P-POSSUM is a better predictor of mortality than POSSUM. Overall, morbidity and mortality risk were found to be significantly higher with delayed hospital presentation and deranged creatinine levels.